Influence of upstream disturbances on performance of an LDV-based cryogenic flow meter standard – CFD modelling and preliminary measurements with air. (August 2021) - Sluše, Jan; Maury, Rémy; Olsen, Åge Andreas Falnes; Geršl, Jan; Kenbar, Asaad
Abstract: Increasing trade of liquefied natural gas (LNG) imposes stringent requirements for accurate flow rate measurement of this high energy content fluid. To satisfy this demand, a flow meter has been developed by CEASAME Exadebit which is based on velocity measurement behind a contraction nozzle using Laser Doppler Velocimetry technique (LDV). For this instrument, a calibration factor is defined relating the measured velocity to the flow rate. This calibration factor depends on the Reynolds number and it can be sensitive to the velocity profile behind the nozzle outlet and to presence of upstream flow disturbances such as bends, valves, etc. when the meter is installed on-site. In this paper, CFD modelling, using OpenFoam software, was employed to analyse the sensitivity of the calibration factor to flow disturbances for two types of disturbing elements; a U-bend and half-plate orifice. The CFD model was validated by comparison with experimental data for the calibration factor and velocity profiles obtained from preliminary LDV measurements with air. Two measurement setups were considered where the velocity is measured either in one point at the nozzle axis or integrated along a line across the nozzle diameter. The results show that the considered disturbing elements cause deviations in the calibration factor in the order of tenths of percent and that the maximal sensitivity of the line-setup to these disturbances is approximately half of the maximal sensitivity of the point-setup. On the other hand, it was shown that the line-setup is more sensitive to the LDV positioning than the point-setup. Highlights: Flow metering using LDV velocity measurement behind a contraction nozzle was studied. Influence of upstream disturbances was investigated using CFD modelling in OpenFOAM. Flow determined from velocity in centre or along a line across the nozzle is compared. Reynolds number dependence for line-method is much weaker than for centre-method. Upstream disturbances cause deviations in calibration factor of tenths of percent.